APPLICATION OF THE PRINCIPLES OF PLAY WHILE LEARNING IN DEVELOPING MULTIPLE INTELLIGENCE IN EARLY CHILDREN'S EDUCATION - Muhammad Nasir; Husin; Maria Ulfah; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
Learning while playing, playing while learning is the principle of fun learning in PAUD. Early age at school is an effective age for developing various potentials that children have. This research is motivated by a problem, namely the application of the principle of playing while learning is still not optimal in developing multiple intelligences in early childhood. This study aims to stimulate children's brains in the long term, so that their memories are always filled with activities that give positive impressions and of course are fun for children, and to find out the Early Childhood Education (PAUD) teacher's feelings about the concept of playing while learning for early childhood. The purpose of playing is basically directed at developing children's multiple intelligences. The principle of playing while learning prioritizes playing activities rather than learning, meaning that learning activities in PAUD are more dominated by fun and exciting activities for children. The theoretical foundations in this study are: the concept of playing while learning, the notion of learning, the concept of PAUD learning, the concept of early childhood education. The approach method used in this study is a qualitative approach. The results of the study show that PAUD Dharma Bakti uses the method of playing while learning to increase the multiple intelligences of children. The conclusion of this study is that learning while playing is very effective to do. The theoretical foundations in this study are: the concept of playing while learning, the notion of learning, the concept of PAUD learning, the concept of early childhood education. The approach method used in this study is a qualitative approach. The results of the study show that PAUD Dharma Bakti uses the method of playing while learning to increase the multiple intelligences of children. The conclusion of this study is that learning while playing is very effective to do. The theoretical foundations in this study are: the concept of playing while learning, the notion of learning, the concept of PAUD learning, the concept of early childhood education. The approach method used in this study is a qualitative approach. The results of the study show that PAUD Dharma Bakti uses the method of playing while learning to increase the multiple intelligences of children. The conclusion of this study is that learning while playing is very effective to do.